(3GdeQGLYI eONd eJcGed (B/s - (3CQjfR, Cdajfs; (3dhjc, LjeS s ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2002)
(3egfI GdeQGLYI(B-(3YedjI GdeQGLYI(B-(3JWHjb YedjI GdeQGLYI Ydi OGFQI GdeHjYGJ hGdJMUjd(B-(3eQGLYI fXe JTZjd GdHjGfGJ GdGdcJQhfjI GdeYbOI(B-(3JWHjb YedjI GdeQGLYI Ydi GdOhGFQ GdCNQi(B-(3GSJceGd GdeQGLYI hJbOje GdNOeGJ GdCNQis
Keywords: (3eQGLYI GdMSGHGJ, fXe GdeYdheGJs